Impact of geomagnetically induced current on power grid resiliency under extreme geomagnetic disturbance - Mohammed Khurshid, Zmnako; Ab Aziz, Nur Fadilah; Rhazali, Zeti Akma; Ab Kadir, Mohd Zainal Abidin (Institute of Electrical and Electronics Engineers, 2023)
With the global commitment to achieving net zero carbon emissions by 2050, the importance of transitioning to clean and efficient energy sources has become increasingly crucial. On this note, grid resiliency is crucial for sustainable energy supply because it ensures a reliable and uninterrupted flow of electricity from renewable sources to consumers. By withstanding and recovering quickly from disruptions, the grid can maintain a stable energy supply, support the integration of intermittent renewable sources, and meet the increasing demand for clean energy. This study presents a detailed case study of the extreme geomagnetic disturbance (GMD) impacts on high voltage (HV) power networks in Peninsular Malaysia. The GMD events arise from extreme conditions on the Sun due to solar activity and drive geomagnetically induced current (GIC) in power transmission lines and other technological conductor networks, causing half-cycle saturation of earthed transformers and leading to voltage-control problems or transformer failure. The power system model comprises 54 substations interconnected with 500 kV, 275 kV, and 132 kV transmission lines. The GIC was calculated through the system with respect to different extreme geoelectric field strengths and substation grounding resistance (GR) values using the nodal admittance matrix (NAM) method. The results showed that extreme GMD events can produce intense GIC values across the system, especially at substations located at the edge and middle of the power network, meaning that the Malaysian power grid is not immune to such events. The maximum GIC was obtained at substation 22 with a value of 896 A at field orientation 140°. Also, the results showed that when the GRs of the substations were decreased, the calculated GICs across the system increased.